The dual-track paradox in social welfare—a layered governance perspective - Yujie Zhang (Humanities & Social Sciences Communications)
Abstract This study investigates the dual-track paradox in China’s welfare governance, where formal state-led programs and informal relational strategies coexist and interact. Using the 2021 Chinese Social Survey data (N = 9260), it examines how formal social security participation and informal gift-giving behavior relate to individual life stress. Results indicate that while formal participation is associated with lower stress (β = –0.037, p < 0.001), this effect is significantly weaker among rural residents (interaction β = –0.004, n.s.) and those outside public-sector employment (β = –0.012, n.s.). By contrast, reliance on gift-giving—reported by 5.82% of respondents—is positively associated with higher stress (β = 0.103, p < 0.001), particularly when unsuccessful (β = 0.290, p < 0.001). Perceived fairness shows the strongest negative correlation with stress (r = –0.204, p < 0.001), while interpersonal and government trust offer modest buffering effects. Moving beyond a psychological framing, the study conceptualizes stress as an ontological condition emerging from procedural opacity, moral entanglement, and symbolic exclusion. The results suggest that layered governance shapes unequal access and adds relational and emotional strain to welfare navigation. Policy implications include enhancing procedural transparency, recognizing culturally embedded informal practices, and building institutions that address both material inequality and symbolic disenfranchisement.